Performance Determinants - Lydia Tarida Mahdalena, Intan; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
In this case, HR is clearly not the main asset but rather a well-defined and expandable asset, compared to the investment portfolio, and not vice versa as a liability (loss, expense). From this point of view, HR is an investment for a more mature institution or organization. The results of this research are as follows: Communication has a positive and significant effect on employee performance with an original sample value of 0.493 and an ap value of 0.000. Work Quality has a positive and significant effect on Employee Performance with an original sample value of 0.370 and ap value of 0.008. Work Quality has a positive and significant effect on Communication with an original sample value of 0.779 and ap value of 0.000. Work Stress has a negative and insignificant effect on employee performance with an original sample value of -0.026 and ap value of 0.398. Work Stress has a positive and significant effect on communication with an original sample value of -0.176 and p value of 0.016. Work Quality has a positive and significant effect on Employee Performance through Communication with an original sample value of 0.385 and p value of 0.001.